STUDIES OF COOLING WATER DISTRIBUTION INSIDE CONDENSER IN PLTP WAYANG WINDU UNIT 2 THROUGH CFD MODELLING - PRASETYO UTOMO (NIM : 13107135); Pembimbing : Dr. Willy Adriansyah ST, MT, ARI
Energy crisis is one of the main problem for all countries around the word, this problem was encouraged by significant industrial growth especially in Indonesia. One of the potential altenative energy to face energy crisis is developing Geothermal Power Plant. However, there are many obstacle will be faced by Geothermal Power Plant system, one of them is short term effectively used which is only for 50 years (Stefansson, 2000). This problem has been pushed to make some engineering technique for increasing the efficiency of Geothermal Power Plant and optimize the performances. Cold side modification can be made to optimize and increase the efficiency of Geothermal Power Plant. In this Final Project, simulation was made to model cooling water flow inside condenser piping from basin intake pit cooling water into horizontal header of each condenser by using Computational Fluids Dynamics software (CFD). Analysis was started from existing and modification design to get flow characteristic such as nozzle pressure inlet, mass flow rate for each vertical header. The results from simulation will be used for starting data to the next project, modification the nozzle. CFD modeling result on the existing design provides uneven distribution pattern of cooling water, whereas the modification with fillet 160 mm, cooling water distribution pattern become more evenly distributed.